The underlying mechanism between compulsory citizenship behaviors and employee innovative work behaviors and knowledge sharing: A moderated mediation model - Abukhait, Rawan; Khattak, Mohammad Nisar; Shaya, Nessrin; Ramanathan, Usha (Frontiers in Psychology, 2023)
This paper draws on conservation of resources theory to advance the literature on extra-role performance behaviors among academics, particularly innovative work behaviors and knowledge sharing, through the lens of work stressors. We develop a moderated-mediated model based on multi-source, multi-timed, and multi-level data from a sample of 207 academics and 137 direct supervisors in five higher education institutions in the United Arab Emirates. Results show that academics’ compulsory citizenship behaviors positively influence negative affectivity, which, in turn, negatively impacts academics’ innovative work behavior and knowledge sharing. The detrimental effect of compulsory citizenship behaviors on negative affectivity is then positively moderated by passive leadership, which amplifies this relationship. The combined effect of compulsory citizenship behaviors and negative affectivity exerted on innovative work behavior and knowledge sharing are magnified amid the elevated presence of passive leadership, while gender does not significantly influence this association. Pertinent theoretical and managerial implications are discussed.